Penambahan Register pada Form Login Aplikasi Master Data KBM dengan Metode Kriptografi AES - Sri Mulyati; Asep Sucipto Indra Sukma; Dwi Nur Febrianto; Fathul Ghina; Juhaendi Juhaendi; Endar Nirmala (Jurnal Informatika Universitas Pamulang, 2022)
Incorrectly designed login forms can result in malicious credentials being exploited to gain unauthorized access. Designing the appearance of the form is enough to have a role so as not to make the user confused when faced with the login form page. In order to make it easier for users to access certain pages, the user must register first. Register also means the registration process (in the register) or system, with the display of the register on the login form, it will make it easier for users to register individually so that they can enter the application. Because previously the KBM master data login form application did not have a register, the author added a register form on the KBM master data application login form page, and needed to add another label that served as a link to the member registration menu that we had created. To do so, click the Standard tab > Labels (StdCtrls), then change the text on the Properties tab. B. "Click here to register on the registration form (Whida, 2018). After testing the login application and the added registration form, the test did not detect any errors and passed all tests. The results according to this test can be used as a reference to improve your application in sync using what is needed and to ensure that the application we develop works as expected. With the development of the KBM master data application, security needs to be implemented as well, such as the vehicle database in the KBM master data Not guaranteed and there is always a risk of misuse of the KBM Master Data. To mitigate this, Master Data can be protected by using Shuffle Technologies (Cryptography, Encryption). Cryptography is sensitive information and is intended to prevent the use of information transmitted over networks such as LANs and the Internet. Known and used by other people and unauthorized parties. Encryption is a method of encoding a message or information into unreadable text and is closely related to encryption, which is a method to protect a message from being read by third parties. In this study, the author uses the Advanced Encryption Standard (AES) algorithm to create a PHP source code encryption application. The AES algorithm was chosen to provide a high level of security. The development of this registration form uses the AES cryptography method, the results of the development of this registration form have been tested and run well.